Effectiveness of sensory integration-based intervention in autistic children, focusing on Chinese children: a systematic review and meta-analysis - Lyu, Bingchen; Ba, Yi; Ma, De; Liu, Niu; Fu, Limin; Xue, Yaqi (Frontiers in Psychiatry, 2025)
ObjectiveIn recent years, the prevalence of autism spectrum disorder (ASD) has been increasing year by year, bringing huge economic and mental burdens to society and families. Ayres Sensory Integration Intervention (ASI) is a widely used approach in the treatment of ASD. A more common sensory integration approach in China is called sensory integration-based intervention (SIBI), which is developed based on ASI. This study systematically analyzes the effects of SIBI on the sensory integration abilities and autism-related behaviors of autistic children.MethodsWe searched PubMed, Cochrane Library, Web of Science, EBSCO, and CNKI databases from inception to February 2025. Randomized controlled trials (RCTs) using SIBI to improve autistic children were included. After selection, data were extracted on author, year, country, sample size, age, intervention type and duration, and outcome indicators. Quality assessment and data extraction were conducted independently by two researchers. Statistical analyses were performed in Stata 17, including forest plots, funnel plots with Egger’s test for publication bias, and meta-regression for heterogeneity.ResultsA total of 16 studies with 1319 samples were included. The results showed that compared to the control group, SIBI had a positive effect on the total score of sensory integration ability scales for autistic children [mean difference (MD), 11.53; 95% confidence interval (CI) (10.53, 12.53); P<0.5]. Compared to the control group, SIBI also positively improved the total score of the ATEC scale [MD, -16.12; 95% CI (-22.61, -9.64); P<0.05] and the total score of the ABC scale [MD, -16.12; 95% CI (-22.61, -9.64); P<0.05]. The results from Egger’s test and the funnel plot indicated no publication bias. Due to the high heterogeneity (I²>50%) in the results of SIBI intervention on the total ABC score, a meta-regression analysis was conducted. The results of the meta-regression analysis indicated that age was not the source of heterogeneity, while the intervention duration was found to be the source of heterogeneity (β=-0.51, P<0.05, 95% CI [-1.01, -0.01]).ConclusionSIBI can effectively improve the sensory integration ability and autism-related behaviors of autistic children.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420250639991.